2021
DOI: 10.1186/s13018-021-02676-z
|View full text |Cite
|
Sign up to set email alerts
|

Failure load of the femoral insertion site of the anterior cruciate ligament in a porcine model: comparison of different portions and knee flexion angles

Abstract: Background This study compared the failure load of the femoral insertion site of the anterior cruciate ligament between different portions and knee flexion angles. Methods In total, 87 fresh-frozen, porcine knees were used in this study. Three knees were used for histological evaluation; the remaining 84 knees were randomly divided into 4 groups: anterior anteromedial bundle, posterior anteromedial bundle, anterior posterolateral bundle, and poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The porcine knee was consistently flexed at an initial angle of 30°. [ 56 ] Notably, during flexion and extension, the pressure exerted on the medial condyle of the articular disc outweighed that exerted on the lateral condyle. Upon flexion to 60°, the pressure values of the third channel of the medial and lateral condyles were recorded as 68.4 and 40.6 N (voltage amplitudes of 0.9 and 0.65 V).…”
Section: Resultsmentioning
confidence: 99%
“…The porcine knee was consistently flexed at an initial angle of 30°. [ 56 ] Notably, during flexion and extension, the pressure exerted on the medial condyle of the articular disc outweighed that exerted on the lateral condyle. Upon flexion to 60°, the pressure values of the third channel of the medial and lateral condyles were recorded as 68.4 and 40.6 N (voltage amplitudes of 0.9 and 0.65 V).…”
Section: Resultsmentioning
confidence: 99%
“…Observation in this current study showed that the porcine ACL insertion can be divided into two parts, namely the direct insertion and indirect insertion. Yamauchi et al (32) also observed in mature porcine knees that the anterior attachment of the femoral ACL site was a direct insertion and the posterior attachment could be characterized as an indirect insertion. This finding is consistent with the current study, and with previous studies on human knees (17,18,33).…”
Section: Discussionmentioning
confidence: 96%